PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KEGUNAAN DAN PERSEPSI RISIKO TERHADAP MINAT MENGGUNAKAN E-PAYMENT DANA - Septa Nabilah Putri; Herman Paleni (LPPM UNIVERSITAS BINA INSAN, 2025)
Electronic payment systems have transformed financial transactions; however, user adoption among university students remains inconsistent. This study this gap by examining the effects of perceived ease of use, perceived usefulness, and perceived risk on users’ intention to adopt DANA, one of the leading digital wallet providers in Indonesia. Guided by the Technology Acceptance Model (TAM), survey data were collected from 302 Indonesian university students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived ease of use significantly influences both perceived usefulness and behavioral intention, while perceived usefulness strongly predicts perceived risk and user intention. Perceived risk exerts a positive but weaker effect on behavioral intention. Collectively, the model explains 69.6% of the variance in user intention, thereby confirming the explanatory power of TAM in the context of digital wallets. Theoretically, this study validates and extends TAM by incorporating perceived risk; practically, it offers insights for e-wallet providers and regulators to design digital financial services that are secure, efficient, and user-friendly. The study’s limitation lies in its single-sample focus on university students, which restricts generalizability. Future research should involve a larger and more diverse population and integrate moderating factors such as trust and financial literacy.